2022
DOI: 10.1055/s-0042-1742366
|View full text |Cite
|
Sign up to set email alerts
|

Active FXI Can Independently Predict Ischemic Stroke in Anticoagulated Atrial Fibrillation Patients: A Cohort Study

Abstract: Background Atrial fibrillation (AF) is associated with a prothrombotic state. Presence of active tissue factor (TF), activated factor IX (FIXa) and FXIa in circulating blood contributes to thrombosis. We investigated a prognostic value of these factors in AF patients. Methods In this cohort study, 284 AF patients (aged 63.3 ± 8.8 years) treated with oral anticoagulants were enrolled. Plasma levels of active coagulation factors were evaluated using thrombin generation assay. Concentrations of fibrinog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Atrial Fibrillation (AF) is the most common sustained cardiac rhythm disorder and is associated with a prothrombotic state. It was shown in a cohort study that in long-term follow-up, FXIa level in circulating blood has been associated with poor prognosis such as IS and cardiovascular death in AF patients on anticoagulants (45). Recently, the FXIa inhibitor asundexian at two doses (20 and 50mg daily) showed lower bleeding rates than the active comparator, the FXa inhibitor apixaban 5mg, in a phase II trial in AF at risk for stroke.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Atrial Fibrillation (AF) is the most common sustained cardiac rhythm disorder and is associated with a prothrombotic state. It was shown in a cohort study that in long-term follow-up, FXIa level in circulating blood has been associated with poor prognosis such as IS and cardiovascular death in AF patients on anticoagulants (45). Recently, the FXIa inhibitor asundexian at two doses (20 and 50mg daily) showed lower bleeding rates than the active comparator, the FXa inhibitor apixaban 5mg, in a phase II trial in AF at risk for stroke.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It was shown in a cohort study that in long-term follow-up, the FXIa level in circulating blood has been associated with poor prognosis such as IS and cardiovascular death in AF patients on anticoagulants. 48 Recently, the FXIa inhibitor asundexian at two doses (20 and 50 mg daily) showed lower bleeding rates than the active comparator, the FXa inhibitor apixaban 5 mg, in a phase II trial in AF at risk for stroke. However, it still remains to be further investigated to what extent inhibition of FXI(a) is equally or more effective than established direct oral anticoagulants (DOACs) to prevent thrombotic events and if they could improve long-term prognosis of AF.…”
Section: Theme 1: the “Coagulome” As A Critical Driver Of Cardiovascu...mentioning
confidence: 99%
“…A study by Suri MF et al [15] found a threefold increased risk of ischaemic stroke, and Yang DT et al [16] reported a fivefold increased risk of stroke or transient ischaemic attack (TIA) in patients with elevated FXI levels. Z ąbczyk MT et al [17] recently found that circulating FXIa is associated with increased risk of ischaemic stroke and cardiovascular death in patients with atrial fibrillation (AF) undergoing anticoagulant therapy during long-term follow-up. Finally, elevated FXI levels have been associated with higher risk of all-cause mortality after the first ischaemic stroke [16].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown recently, that in patients with advanced CAD, FXIa was an independent predictor of MI, stroke, or CV death in long-term follow-up [ 20 ]. In patients with atrial fibrillation FXIa was an independent predictor of stroke or CV mortality which occurred despite oral anticoagulation [ 21 ]. The persistent generation of FXIa in the plasma is likely driven by oxidative stress, inflammation, and endothelial injury [ 14 ], all of which are involved in the pathophysiology of DM, suggesting a possible FXI upregulation in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%